Review of Ang Cheng Guan, Southeast Asia’s cold war: An interpretative history - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2018)
Ang Cheng Guan’s Southeast Asia’s Cold War: An Interpretive History makes a welcome scholarly contribution to the field. As he rightly points out in the introduction to his book, the “voluminous” literature concerned with the Cold War in Southeast Asia has too long centered on the United States, European decolonisation, and/or the Sino-Soviet competition for Hanoi’s loyalty.